IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEAD TOGETHER UNTUK MENINGKATKAN PEMAHAMAN KONSEP OPERASI BENTUK ALJABAR PADA SISWA KELAS VII SMP NEGERI 7 CIMAHI - Eka Senjayawati; Ima Saridah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This research is classroom action research. The aim is to improve the understanding of the concept of algebraic operations in Class VII  students of SMP Negeri 7 Cimahi by using the number head together type of cooperative learning model. This research was conducted on students of class VII I SMP Negeri 7 Cimahi with a total of 30 students. The instrument used is in the form of test questions for understanding mathematical concepts regarding the operation of algebraic forms and questionnaire sheets. Implementation stage: conducting initial test (before action), test cycle I and II (giving action). In the first cycle with a direct learning model. Then in the second cycle with the NHT type cooperative learning model. The results of this study indicate that there is an increase in students' understanding of mathematical concepts, with test results above the KKM.